Training and testing physical capacities for elite soccer players - Hoff, J. (Journal of Sports Sciences, 2005)
Elite soccer players spend a substantial amount of time trying to improve physical capacities, including aerobic endurance and strength and the strength derivatives of speed and power. The average oxygen uptake for international soccer teams ranges from 55 to 68 ml· kg-1 · min-1 and the half-squat maximal strength from 120 to 180 kg. These values are similar to those found in other team sports. Recently, it has been shown that the heart's stroke volume is the element in the oxygen chain that mainly limits aerobic endurance for athletes. These findings have given rise to more intensive training interventions to secure high stroke volumes, which, in turn, have proved positive in changing both maximal oxygen consumption and soccer performance in terms of distance covered, contacts with the ball and number of sprints in a game. The training employed has consisted of 4 × 4-min "intervals" running uphill at 90-95% of maximal heart rate interspersed with 3 min jogging at 70% of maximal heart rate to facilitate removal of lactate. Research has revealed that a soccer-specific training routine with the ball might be as effective as plain running. Strength training to produce neural adaptations has been effective in changing not only strength in terms of "one-repetition maximum", but also sprinting velocity and jumping height, in elite soccer players without any change in body mass. The same training has also improved running economy and thus aerobic endurance performance. The training regimen used for a European Champions League team was 4 × 4 repetitions of half-squats with the emphasis on maximal mobilization of force in the concentric action.